MDM : Fundamentals, Security, and the Modern Desktop: Using Intune, Autopilot, and Azure to Manage, Deploy, and Secure Windows 10 - Moskowitz, Jeremy; Rose, Stephen (Indianapolis, Indiana : John Wiley & Sons, Inc. (trade) : Sybex, 2019)
A must-read for IT Admins leveraging Modern Management with MDM, this book teaches you MDM fundamentals, essential troubleshooting techniques, and how to manage your enterprise desktops. --
Enterprise mobility and MDM essentials -- Set up Azure AD and MDM -- MDM profiles, policies, and groups -- Co-management and co-policy management -- MDM migration and MDM troubleshooting -- Deploying software and scripts -- Enterprise state roaming and OneDrive for business -- Rollouts and refreshes with configuration designer and Autopilot -- Windows 10 health and happiness: servicing, readiness, analytics, and compliance -- Security with baselines, BitLocker, AppLocker, and conditional access -- MDM add-on tools : free and pay.
Online resource; title from PDF file page (EBSCO, viewed July 8, 2019).
John Wiley and Sons
Keywords: Mobile communication systems; Mobile computing; Radiocommunications mobiles; Informatique mobile; Mobile communication systems; Mobile computing